+0  
 
0
86
2
avatar

In triangle ABC, angle B is right.  E is on AC and F is on BC such that EF is parallel to AB.  If AB = 8, BC = 6, and AE = x, then find the perimeter of triangle EFC in terms of x.

 May 15, 2020

Best Answer 

 #1
avatar+2422 
+3

It is vitally important to use a diagram, I would say. Luckily, I have taken the time to create one for you so that you can follow along. I have put all the information we know into the diagram below:

 

 

In order to find the perimeter, we need to express the length of each side of \(\triangle EFC\) in terms of x. \(\angle B\) is a right triangle, so by Pythagorean's theorem, \(AC=10\) and \(EC = 10-x\).

 

\(\triangle ACB \cong \triangle ECF \) by Angle-Angle Similarity Postulate, and we will use this similarity in order for us to express the remaining side lengths in terms of x like so:

\(\frac{10-x}{10}=\frac{EF}{8}\quad\quad\quad\frac{10-x}{x}=\frac{CF}{6}\\ EF = 8-\frac{4}{5}x\quad\quad CF=6-\frac{3}{5}x\) 

 

Now, find the perimeter by taking the sum of all the sidelngths of the desired triangle.

 

\(P=EC+EF+CF\\ P=(10-x)+(8-\frac{4}{5}x)+(6-\frac{3}{5}x)\\ P=24-\frac{12}{5}x\)

 May 15, 2020
 #1
avatar+2422 
+3
Best Answer

It is vitally important to use a diagram, I would say. Luckily, I have taken the time to create one for you so that you can follow along. I have put all the information we know into the diagram below:

 

 

In order to find the perimeter, we need to express the length of each side of \(\triangle EFC\) in terms of x. \(\angle B\) is a right triangle, so by Pythagorean's theorem, \(AC=10\) and \(EC = 10-x\).

 

\(\triangle ACB \cong \triangle ECF \) by Angle-Angle Similarity Postulate, and we will use this similarity in order for us to express the remaining side lengths in terms of x like so:

\(\frac{10-x}{10}=\frac{EF}{8}\quad\quad\quad\frac{10-x}{x}=\frac{CF}{6}\\ EF = 8-\frac{4}{5}x\quad\quad CF=6-\frac{3}{5}x\) 

 

Now, find the perimeter by taking the sum of all the sidelngths of the desired triangle.

 

\(P=EC+EF+CF\\ P=(10-x)+(8-\frac{4}{5}x)+(6-\frac{3}{5}x)\\ P=24-\frac{12}{5}x\)

TheXSquaredFactor May 15, 2020
 #2
avatar+111456 
0

Very nice, X^2    !!!!!!

 

 

 

cool cool cool

 May 15, 2020

70 Online Users

avatar